2012
DOI: 10.1161/circimaging.111.966986
|View full text |Cite
|
Sign up to set email alerts
|

Systemic-to-Pulmonary Collateral Flow, as Measured by Cardiac Magnetic Resonance Imaging, Is Associated With Acute Post-Fontan Clinical Outcomes

Abstract: Background Systemic-pulmonary collateral (SPC) flow occurs commonly in single ventricle patients after superior cavo-pulmonary connection, with unclear clinical significance. We sought to evaluate the association between SPC flow and acute post-Fontan clinical outcomes using a novel method of quantifying SPC flow by cardiac magnetic resonance (CMR). Methods and Results All patients who had SPC flow quantified by CMR prior to Fontan were retrospectively reviewed to assess for acute clinical outcomes after Fon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(50 citation statements)
references
References 28 publications
4
46
0
Order By: Relevance
“…These results are similar to those of Glatz et al 11 who also measured SPC flow by CMR prior to a Fontan operation and demonstrated that, after adjustment for Fontan type and fenestration, higher SPC flow was associated with dichotomous outcome variables including hospital duration ≥7 days (OR 9.2) and pleural drainage duration ≥10 days (OR 22.7). Linear relationships with outcome variables were either absent or less robust.…”
Section: Spc Flow and Fontan Outcomessupporting
confidence: 88%
“…These results are similar to those of Glatz et al 11 who also measured SPC flow by CMR prior to a Fontan operation and demonstrated that, after adjustment for Fontan type and fenestration, higher SPC flow was associated with dichotomous outcome variables including hospital duration ≥7 days (OR 9.2) and pleural drainage duration ≥10 days (OR 22.7). Linear relationships with outcome variables were either absent or less robust.…”
Section: Spc Flow and Fontan Outcomessupporting
confidence: 88%
“…Also, although we used advanced imaging techniques, there are some inherent limitations in spatial resolution that could affect the measurements. We did not take aortopulmonary collateral flow into account, which has been demonstrated in recent reports to be substantial and clinically relevant in some cases [36][37][38], and which could potentially have a measurable effect on TCPC energetics. All computational simulations were carried out with time-averaged flow rates and rigid vessel walls, and even though these methods provide a good approximation to the in vivo case [20,39], they may not be physiologically precise.…”
Section: Commentmentioning
confidence: 99%
“…Highlighting the clinical significance of APC flow, three studies recently demonstrated that increased collateral flow before the Fontan operation was associated with longer duration of pleural drainage and prolonged recovery in the postoperative period [6][7][8]. However, the mentioned studies primarily focused on technical aspects of quantifying APC flow [2][3][4] or were assessed in patients after the Glenn-procedure [6][7][8].…”
Section: Introductionmentioning
confidence: 99%